2019
DOI: 10.1101/576819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epistasis detection and modeling for genomic selection in cowpea (Vigna unguiculata. L. Walp.)

Abstract: 15Genetic architecture reflects the pattern of effects and interaction of genes underling 16 phenotypic variation. Most mapping and breeding approaches generally consider the additive 17 part of variation but offer limited knowledge on the benefits of epistasis which explains in 18 part the variation observed in traits. In this study, the cowpea multiparent advanced 19 generation inter-cross (MAGIC) population was used to characterize the epistatic genetic 20 architecture of flowering time, maturity, and seed … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 99 publications
2
12
1
Order By: Relevance
“…Result further showed that students did not differ significantly in test anxiety with respect to their sex. Result of present study contradicted to the findings of many previous studies (Rana and Mahmood, 2010;Erdem, 2007;Hashmat et al, 2008) though other studies (Ndirangu, et al, 2009;Olatoye, 2009;Faleye 2010) outlined the findings similar to the results of present study. In present study, despite the fact that students did not differ statistically in terms of test anxiety, female students were having higher test anxiety as compared to their male counterpart.…”
Section: Resultscontrasting
confidence: 92%
“…Result further showed that students did not differ significantly in test anxiety with respect to their sex. Result of present study contradicted to the findings of many previous studies (Rana and Mahmood, 2010;Erdem, 2007;Hashmat et al, 2008) though other studies (Ndirangu, et al, 2009;Olatoye, 2009;Faleye 2010) outlined the findings similar to the results of present study. In present study, despite the fact that students did not differ statistically in terms of test anxiety, female students were having higher test anxiety as compared to their male counterpart.…”
Section: Resultscontrasting
confidence: 92%
“…The two FEM models used in BLINK were the following In this study, we focused on the SNPs associated with the tolerance index trait. However, we rerun the traits investigated by Huynh et al 20 and Olatoye et al 22 using BLINK and the SNPs identified for these traits were analyzed in the network analysis section. LD heatmaps were established in R® v.3.6.1 using the package 'LDheatmap' 39 .…”
Section: Genome-wide Association Studymentioning
confidence: 99%
“…The nodes in the network corresponded to the traits and the significant SNPs associated with each trait. The traits investigated by Huynh et al 20 and Olatoye et al 22 were represented by solid circles, whereas the tolerance index traits were visualized by solid diamonds. The SNPs associated with each trait were denoted using solid dark grey circles.…”
Section: Association Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Olatoye et al (2019) ‘Epistasis detection and modeling for genomic selection in cowpea (Vigna unguiculata. L.…”
Section: Acknowledgmentsmentioning
confidence: 99%